MENINGKATKAN HASIL BELAJAR PKN PADA SISWA KELAS V MELALUI STRATEGI INDEX CARD MATCH (MATERI MENGHARGAI DAN MENAATI KEPUTUSAN BERSAMA) DI MIN PEMBANTANAN - Mariatul Kiptiyah (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2015)
Selection of appropriate teaching strategies must be in various. It is good and should be in accordance with the purpose of teaching - should be achievable. Teaching strategy is the first step that must be taken by a teacher in achieving the learning objectives. The conducted research on improving fifth grade student learning outcomes in Civics (PKn) through a strategy of Index Card Match (Material: Respect and Comply the Joint Decision) in MIN Pembantanan. This research was conducted through Class Action Research (PTK). This class action research aims to improve and enhance learning outcomes of subjects Civics on “Respect and Comply the Joint Decision” material for students in class VA MIN Pembantanan Sungai Tabuk Banjar district. PTK is implemented through two cycles to see the increasing of student learning outcomes and activities in subjects Civics on “respect and Compley the Joint together” material through Index Card Match strategy. The subjects in this class action research is graders VA MIN Pembantanan , 27 students consists of 14 male students and 13 female students. The object of this study is the implementation of learning strategy : “Index Card Match” in improving students’ learning outcomes in class VA on subjects Civics on Respect and Comply joint decisions material in MIN Pembantanan Sungai Tabuk. The type of data is divided into two parts, namely quantitative and qualitative data. The source of the data in this study were drawn from several sources, they are the students, teachers, and colleagues and collaborators. Research instruments in this research include tests, interviews, questionnaires, and discussions. This study revealed unacceptable or in other words, this study declared successful.